ANT colony optimization for controller and sensor-actuator location in active vibration control - Md Nor, Khairul affendy; Abdul Muthalif, Asan Gani; Walid, Azni N. (Multi-Science Publishing Company, 2013)
Developing light weight yet stronger and more flexible panels in aircraft structure to withstand from failure due to vibration has been the interest of many researchers nowadays. Piezoelectric material has been the popular choice to attenuate vibration actively and numerous techniques of optimal control and actuator placement have been proposed. This paper discusses on active vibration control of a simply supported thin plate excited and actuated by piezoelectric patches. Mathematical model of the simply supported plate with piezoelectric patches is derived using Euler-Bernoulli model. The main focus is to find the optimal location of the collocated sensor-actuator and controller gains using a swarm intelligent algorithm called Ant Colony Optimization (ACO) which later verified with Genetic Algorithm (GA). A simply supported plate is taken as a benchmark model to perform simulation study.